Explaining People’s Worry Levels During the Covid-19 Pandemic: An Analysis of Socio-Economic and Cultural Dimensions - Rojas-Méndez, José I. (Frontiers in Psychology, 2021)
This paper examines the influence of socio-economic and cultural dimensions (measured at the country level) on what concerns people the most about the Covid-19 pandemic. Based on secondary data, the study considers the opinion of more than 24,000 individuals living in 30 different countries, with national samples weighted to match each country's general population older than 18 years of age. A set of linear Bayesian regressions was applied to 10 different types of worries reported for economic, health and safety domains. Results demonstrate that socio-economic variables and cultural dimensions complement each other in explaining people's concerns about the effect of the Covid-19 pandemic. An overall view of the analysis also reveals that cultural dimensions exceed socio-economic variables in explaining peoples' worries about health and safety domains. Socio-economic variables are slightly more effective in explaining the worries of the economic domain. Among the cultural dimensions, long-term orientation and uncertainty avoidance are the best in explaining people's worries. The higher the score in long-term orientation, the lower the worry levels expressed by the respondents. Likewise, low scores on uncertainty avoidance generate lower levels of worries due to the Covid-19 pandemic. Finally, health worries produce a positive outcome because they explain a significant reduction in the fatality rate.